Oligomeric quaternary ammonium salt grafted nanometer ferroferric oxide, preparation method and oil-water separation application thereof

CN118577012BActive Publication Date: 2026-10-20XI'AN PETROLEUM UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410633616.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-21
Publication Date
2026-10-20
Estimated Expiration
2044-05-21

AI Technical Summary

Technical Problem

[0004]为解决现有破乳剂试剂用量大的破乳问题,本发明的目的是提供了一种低聚季铵盐接枝的纳米四氧化三铁及制备方法和油水分离应用,该方法制备的纳米四氧化三铁作为纳米粒子破乳剂,具有普适性强、使用剂量低的优点

Benefits of technology

[0022]本发明以纳米Fe3O4为磁性基质,硅烷偶联为中间媒介,接枝低聚季铵盐,提供了一种普适性较强、使用剂量低、制备条件温和的低聚季铵盐修饰的磁性纳米四氧化三铁颗粒,对纳米四氧化三铁表面电荷和润湿性联合调控,结合低聚季铵盐优异的破乳效果,将聚阳离子引入体系,相比于传统破乳剂需要在高温高压的条件下合成,低聚季铵盐在55-70℃便可引发聚合反应,且分子量适中、稳定性良好,更容易包裹在磁性纳米颗粒的表面。对纳米四氧化三铁进行表面接枝改性,调控纳米颗粒的润湿性,通过SEM和接触角分析得出Fe3O4@KH550@MD3为粗糙表面,同时含有亲水域和亲油域,Fe3O4@KH550@MD3在2D毛细管效应的拉力下覆盖过各自的油水结构域,从而达到超双亲的润湿状态,大大提升了破乳效果。针对至少三种不同类型的油水体系进行破乳,降低了使用剂量,扩大了纳米颗粒的适用范围。本发明为处理含油废水、W/O和O/W原油乳液、含泥O/W原油乳液的破乳提供了新思路,改善了传统破乳剂专一性强的问题,同时为超双亲材料的制备提供了新途径。本发明合成步骤简单,条件温和,从实用性、绿色性、高效性以及合成破乳剂难度多方面具有潜在的应用前景,有望应用于油田大规模生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118577012B_ABST
    Figure CN118577012B_ABST
Patent Text Reader

Abstract

The application discloses oligomeric quaternary ammonium salt grafted nano Fe3O4 and a preparation method and oil-water separation application thereof, and relates to the following steps: mixing nano Fe3O4 and a silane coupling agent, and then performing a hydrolysis reaction to obtain an intermediate Fe3O4@KH550; performing one-pot reaction of the intermediate Fe3O4@KH550, epichlorohydrin and an organic amine to obtain an unblocked substance; adding the unblocked substance into an ethanol solution of a blocking agent to perform a blocking reaction, and thus obtaining oligomeric quaternary ammonium salt grafted nano Fe3O4. The nano Fe3O4 is subjected to surface grafting modification, the wettability of the nano particles is regulated, the nano particles have the characteristics of super amphiphilicity, the demulsification effect is greatly improved, at least three different types of oil-water systems are subjected to demulsification, the use dosage is reduced, and the application range of the nano particles is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of oilfield chemical synthesis materials technology, specifically relating to an oligomeric quaternary ammonium salt-grafted nano-ferric oxide, its preparation method, and its application in oil-water separation. Background Technology

[0002] Crude oil extraction and transportation generate large quantities of oil-water emulsions. These stable emulsions reduce equipment lifespan through corrosion, and the discharged oily wastewater pollutes the environment. Traditional demulsifiers suffer from problems such as high specificity, strong resistance, large reagent consumption, secondary pollution, and difficulty in recycling. Therefore, developing novel functional magnetic demulsifiers with small reagent consumption, good demulsification effect, and recyclability is of great significance in the field of oil-water separation. The structural barriers and electrostatic repulsion within the emulsion space make it difficult to separate emulsions using traditional methods or technologies.

[0003] Based on O / W emulsions, Soheila's team synthesized Fe3O4@OA / GO nanocomposites, achieving oil-water separation at 600ppm–1000ppm for up to 6 cycles, but requiring a large dosage. Wamda utilized silica-encapsulated magnetic Fe3O4 nanoparticles to demulsify O / W emulsions, achieving 9 cycles, but it is only suitable for emulsions with low oil content. Based on W / O emulsions, Jia et al. synthesized a polyether-functionalized magnetic nano-demulsifier. Fe3O4@CF achieved a demulsification and dehydration rate of 96.68% at 600ppm, 65℃, 120min, and pH=6, achieving 5 cycles. Soheila's team synthesized an amphiphilic magnetic nano-demulsifier, MND, with a WCA of 58° and an OCA of 76.6°. At 1900ppm, 80℃, and 5min, the demulsification and dehydration rate ranged from 82.14% to 99.3%, achieving 6 cycles. Liu et al. prepared a magnetic composite demulsifier (Fe3O4@C–F). Under conditions of 800 ppm, 65℃, 90 min, and pH=6, the Fe3O4@CF magnetic demulsifier achieved a dehydration rate of 91.68% and could be recycled up to 6 times. In summary, regarding the demulsification problem of W / O and O / W emulsions, nano-ferric oxide mainly achieves surface modification through grafting with polyethers and other nanomaterials, allowing for recycling. However, it suffers from drawbacks such as large dosage requirements, difficult synthesis, strong system specificity, narrow pH range, and high demulsification temperature. Summary of the Invention

[0004] To address the problem of high dosage in existing demulsifiers, the present invention aims to provide a method for preparing oligomeric quaternary ammonium salt-grafted nano-ferric oxide and its application in oil-water separation. The nano-ferric oxide prepared by this method, as a nanoparticle demulsifier, has the advantages of strong versatility and low dosage.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0006] A method for preparing oligomeric quaternary ammonium salt-grafted nano-ferric oxide includes the following steps:

[0007] Nano-iron oxide and silane coupling agent were mixed and then hydrolyzed to obtain intermediate Fe3O4@KH550.

[0008] The intermediate Fe3O4@KH550, epichlorohydrin and organic amine were reacted in a one-pot process to obtain an uncapped substance.

[0009] Uncapped material was added to an ethanol solution of the capping agent to carry out a capping reaction, resulting in nano-iron oxide grafted with oligomeric quaternary ammonium salt.

[0010] Furthermore, the silane coupling agent is KH550 or KH570.

[0011] Furthermore, the molar ratio of nano-ferric oxide to silane coupling agent is 1:(3-10).

[0012] Furthermore, the hydrolysis reaction is carried out at a temperature of 30-60℃ for 6-8 hours.

[0013] Furthermore, the molar ratio of epichlorohydrin, organic amine and intermediate Fe3O4@KH550 is 1:(1.6-2):(0.02-0.06).

[0014] Furthermore, the organic amine is dimethylamine, triethylenetetramine, tetraethylenepentamine, or polyethyleneimine with a molecular weight of 600-3000.

[0015] Furthermore, the one-pot reaction temperature is 55-70℃, and the time is 6-8 hours.

[0016] Furthermore, the capping agent is bromoethane, bromohexane, bromooctane, bromododecane, or benzyl bromide;

[0017] The amount of capping agent used is 3-5 times the amount of organic amine.

[0018] The end-capping reaction is carried out at a temperature of 60-80℃ for 4-6 hours.

[0019] A nano-iron oxide grafted with oligomeric quaternary ammonium salt.

[0020] Application of oligomeric quaternary ammonium salt-grafted nano-ferric oxide as a demulsifier in oil-water separation.

[0021] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0022] This invention uses nano-Fe3O4 as a magnetic matrix and silane coupling as an intermediate medium to graft oligomeric quaternary ammonium salts, providing a versatile, low-dosage, and mildly prepared magnetic nano-Fe3O4 modified with oligomeric quaternary ammonium salts. It combines the surface charge and wettability of nano-Fe3O4 with the excellent demulsification effect of oligomeric quaternary ammonium salts, introducing polycations into the system. Compared to traditional demulsifiers that require high temperature and high pressure for synthesis, oligomeric quaternary ammonium salts can initiate polymerization reactions at 55-70℃, and have a moderate molecular weight and good stability, making them easier to coat the surface of magnetic nanoparticles. Surface grafting modification of nano-Fe3O4 controls the wettability of the nanoparticles. SEM and contact angle analysis show that Fe3O4@KH550@MD3 has a rough surface containing both hydrophilic and oleophilic domains. Under the pull of the 2D capillary effect, Fe3O4@KH550@MD3 covers both oil and water domains, achieving a superamphilic wettability state and greatly improving the demulsification effect. This invention demulsifies at least three different types of oil-water systems, reducing the dosage required and expanding the applicability of nanoparticles. It provides a new approach for demulsifying oily wastewater, W / O and O / W crude oil emulsions, and mud-containing O / W crude oil emulsions, improving upon the high specificity of traditional demulsifiers and offering a new route for the preparation of superamphilic materials. The synthesis steps are simple and the conditions are mild. It has potential applications in terms of practicality, environmental friendliness, high efficiency, and the difficulty of synthesizing demulsifiers, and is expected to be applied to large-scale oilfield production.

[0023] Furthermore, the present invention uses different bromoalkanes, namely bromohexane, bromoethane, bromooctane, or bromododecane, to end the molecules. This is because the long oily chains at the oil-water interface make the molecules more amphiphilic and wettable. Alkyl chains of different lengths have different hydrophobic effects, which conforms to the size effect and is more conducive to the demulsification of emulsified oils. Attached Figure Description

[0024] Figure 1 This invention provides a synthetic route for nano-ferric oxide grafted with oligomeric quaternary ammonium salts.

[0025] Figure 2 The infrared spectra of oligomeric quaternary ammonium salt-grafted nano-Fe3O4 (Fe3O4@KH550@MD2, Fe3O4@KH550@MD3, Fe3O4@KH550@MD4, Fe3O4@KH550@MD5) prepared in this invention are shown below; (a) is the FT-IR of Fe3O4@KH550, (b) is the FT-IR of Fe3O4@KH550@MD2, (c) is the FT-IR of Fe3O4@KH550@MD4, and (d) is the FT-IR of Fe3O4@KH550@MD3 compared with the raw material Fe3O4 and the intermediate Fe3O4@KH550.

[0026] Figure 3 The XRD diffraction patterns of the oligomeric quaternary ammonium salt-grafted nano-Fe3O4 (Fe3O4@KH550@MD2, Fe3O4@KH550@MD3, Fe3O4@KH550@MD4, Fe3O4@KH550@MD5) prepared in this invention are shown.

[0027] Figure 4 XPS spectra of Fe3O4@KH550@MD3 and Fe3O4@KH550@MD5 prepared in this invention; wherein, (a) is the total XPS spectrum of Fe3O4@KH550@MD3 and Fe3O4@KH550@MD5, (b) is the C1S spectrum of Fe3O4@KH550@MD3, (c) is the C1S spectrum of Fe3O4@KH550@MD5, (d) is the O1S spectrum of Fe3O4@KH550@MD3, (e) is the O1S spectrum of Fe3O4@KH550@MD3, (f) is the N1S spectrum of Fe3O4@KH550@MD3, (g) is the O1S spectrum of Fe3O4@KH550@MD5, and (h) is the Fe3O4@KH550@MD3 Fe 2P spectra, (i) is the 2P spectrum of Fe3O4@KH550@MD5 Fe;

[0028] Figure 5 The demulsification effect of a series of MNPs on O / W emulsions (high-sulfur crude oil from Changqing Oilfield) is shown in the figure. Among them, (a) is the standard curve, (b) is the light transmittance of the lower water layer of the Fe3O4@KH550@MD series products, (c) is the demulsification effect of Fe3O4@KH550@MD2, (d) is the demulsification effect of Fe3O4@KH550@MD3, (e) is the demulsification effect of Fe3O4@KH550@MD4, and (f) is the demulsification effect of Fe3O4@KH550@MD5.

[0029] Figure 6 Fe3O4@KH550@MD3 and Fe3O4@KH550@MD5 are used to target the demulsification effect of oily wastewater; among them,

[0030] (a) The demulsification effect of different doses of Fe3O4@KH550@MD3 and Fe3O4@KH550@MD5 at 60℃ for 1 hour.

[0031] (b) The demulsification effect of Fe3O4@KH550@MD and Fe3O4@KH550@MD5 at different pH, 1 h, and 60℃; (c) The demulsification effect of Fe3O4@KH550@MD3 and Fe3O4@KH550@MD5 at different salinity, 1 h, and 60℃; (d) The effect of different concentrations of hydrogen peroxide on the demulsification effect of Fe3O4@KH550@MD3 and Fe3O4@KH550@MD5 at 1 h and 60℃; (e) Five-cycle demulsification experiment of Fe3O4@KH550@MD3 and Fe3O4@KH550@MD5.

[0032] Figure 7 The effects of different proportions of Fe3O4@KH550@MD3 and Fe3O4@KH550@MD3+T2-MD4 on the demulsification of oil-cement (O / W) emulsions were investigated.

[0033] Figure 8 Photographs show the oil-water contact angles of Fe3O4@KH550@MD3. (a) shows the contact angle between Fe3O4@KH550@MD3 synthesized from oligomeric quaternary ammonium salt and intermediate Fe3O4@KH550 at a molar ratio of 1:10 and distilled water, with WCA = 18°. (b) shows the contact angle between Fe3O4@KH550@MD3 synthesized from oligomeric quaternary ammonium salt and intermediate Fe3O4@KH550 at a molar ratio of 1:25. The contact angle of @MD3 with distilled water, WCA = 9.75°; (c) is the contact angle of Fe3O4@KH550@MD3 synthesized by a molar ratio of oligomeric quaternary ammonium salt and intermediate Fe3O4@KH550 of 1:50 with distilled water, WCA = 9.50°; (d) is the contact angle of Fe3O4@KH550@MD3 synthesized by a molar ratio of oligomeric quaternary ammonium salt and intermediate Fe3O4@KH550 of 1:100. 3. Contact angle with distilled water, WCA = 0°; (e) is the contact angle of Fe3O4@KH550@MD3 synthesized by a molar ratio of oligomeric quaternary ammonium salt and intermediate Fe3O4@KH550 of 1:10 with kerosene, OCA = 8.04°; (f) is the contact angle of Fe3O4@KH550@MD3 synthesized by a molar ratio of oligomeric quaternary ammonium salt and intermediate Fe3O4@KH550 of 1:25 with kerosene. The contact angle (g) of Fe3O4@KH550@MD3 synthesized with an oligomeric quaternary ammonium salt and intermediate Fe3O4@KH550 in a molar ratio of 1:50 is 6.5°, and the contact angle (h) of Fe3O4@KH550@MD3 synthesized with an oligomeric quaternary ammonium salt and intermediate Fe3O4@KH550 in a molar ratio of 1:100 is 0°.

[0034] Figure 9The images show the SEM morphology of Fe3O4@KH550@MD3, where (a) is the SEM morphology image and (b) is the particle size distribution. Detailed Implementation

[0035] To facilitate understanding of the present invention, a more complete description will be given below with reference to the accompanying drawings. Preferred embodiments of the invention are shown in the drawings. However, the invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of the invention.

[0036] In this invention, the oligomerization in the oligomeric quaternary ammonium salt-grafted nano-ferric oxide refers to a degree of polymerization of 15 to 30.

[0037] To achieve efficient demulsification of complex oil-water systems in oilfields, this invention uses nano-Fe3O4 as a magnetic matrix and silane-coupled KH550 as an intermediate medium, grafting oligomeric quaternary ammonium salts to develop a versatile, low-dosage, and mildly prepared magnetic nano-Fe3O4@KH550@MD2, Fe3O4@KH550@MD3, Fe3O4@KH550@MD4, Fe3O4@KH550@MD5. The structure of the nanoparticles was characterized by Fourier transform infrared (FTIR), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS). Furthermore, by jointly regulating the surface charge and wettability of nano-ferric oxide, and combining this with the excellent demulsification effect of oligomeric quaternary ammonium salts, polycationic compounds are introduced into the system. Compared to traditional demulsifiers that require high temperature and high pressure for synthesis, oligomeric quaternary ammonium salts can initiate polymerization reactions at 55-70℃, and have moderate molecular weight and good stability, making them easier to coat the surface of magnetic nanoparticles. Surface grafting modification of nano-ferric oxide further regulates the wettability of the nanoparticles, giving them superamphilic properties, which greatly improves the demulsification effect. This allows for demulsification of at least three different types of oil-water systems, reducing the dosage required and expanding the applicability of the nanoparticles.

[0038] See Figure 1 The present invention discloses a method for preparing nano-ferric oxide grafted with oligomeric quaternary ammonium salt, comprising the following steps:

[0039] 1) Nano-sized iron(III) oxide (20nm-50nm) sonicated in 15-20mL distilled water for 15-30min and silane coupling agent (KH550 or KH570) were hydrolyzed in a three-necked flask at a molar ratio of 1:(3-10) and mechanically stirred at 30-60℃ for 8h. After washing with an appropriate amount of ethanol, the mixture was vacuum dried at 40-60℃ for 8-10h to obtain the intermediate Fe3O4@KH550;

[0040] The molecular weight of nano-ferric oxide is 231.5, and the molecular weight of silane coupling agent KH550 is 221.37.

[0041] 2) The intermediate Fe3O4@KH550 was sonicated in 15-20 mL of distilled water for 15-30 min, and then reacted with epichlorohydrin and an organic amine (dimethylamine, triethylenetetramine, tetraethylenepentamine, or polyethyleneimine with a molecular weight of 600, 1800, or 3000) in a one-pot reaction in a three-necked flask. The mixture was heated in a water bath at 55-70℃ with mechanical stirring and reflux for 6-8 hours to obtain the uncapped material.

[0042] The molar ratio of epichlorohydrin, organic amine and intermediate Fe3O4@KH550 is 1:(1.6-2):(0.01-0.1).

[0043] 3) Dissolve different brominated end-capping agents in anhydrous ethanol, then add the uncapped material, and react for 4-6 hours under conditions of water bath heating at 60-80℃, mechanical stirring, and reflux. The amount of each brominated end-capping agent is 3-5 times the amount of dimethylamine; the brominated end-capping agents are bromoethane, bromohexane, bromooctane, bromododecane, or benzyl bromide. Wash, centrifuge, and freeze-dry to obtain oligomeric quaternary ammonium salt-grafted nano-Fe3O4, which are superamphilic magnetic nanoparticles.

[0044] Example 1

[0045] First, 1.68 g of iron(III) oxide was ultrasonically dispersed in 15 mL of distilled water for 15 min, and then added to a three-necked flask containing 12.5 mL of silane coupling agent (KH550). After mechanical stirring at 40 °C for 8 h, the product was removed, washed with an appropriate amount of ethanol, and then vacuum dried at 40 °C for 10 h to obtain the intermediate Fe3O4@KH550.

[0046] The second step, the one-pot method: 3.9 mL (0.05 mol) of epichlorohydrin was added dropwise through a constant pressure dropping funnel to a three-necked flask containing 12.5 mL (0.1 mol) of dimethylamine aqueous solution and 0.5 g of Fe3O4@KH550 (0.001 mol). The mixture was heated in a water bath at 60 °C, mechanically stirred, and refluxed for 6 hours to obtain the uncapped substance.

[0047] The third step involved capping the uncapped material by adding 38.6 mL (0.2 mol) of bromooctane to the uncapped material and continuing mechanical stirring in an 80°C water bath, followed by reflux for 4 hours. After the reaction was complete, the product was washed with distilled water (50 mL x 5), centrifuged at 8000 rpm, and then washed again with ethanol (50 mL x 5), centrifuged at 8000 rpm. After discarding the supernatant, the product was removed using a magnet and freeze-dried for 24 hours to obtain polyquaternary ammonium salt-grafted nano-Fe3O4, denoted as Fe3O4@KH550@MD3 (brownish-black powder), with the following structural formula:

[0048]

[0049] See Figure 9 As can be seen from (a) and (b), the prepared demulsifier has a particle size of 46.8 nm, and the nanoparticles are uniform in size and have good dispersion.

[0050] Example 2

[0051] Similar to Example 1, except that the capping agent was 0.2 mol hexane, resulting in polyquaternary ammonium salt-grafted nano-Fe3O4, denoted as Fe3O4@KH550@MD4 (black powder), with the following structural formula:

[0052]

[0053] Example 3

[0054] Similar to Example 1, except that the capping agent was 0.2 mol benzyl bromide, resulting in polyquaternary ammonium salt-grafted nano-Fe3O4, denoted as Fe3O4@KH550@MD2 (brownish-yellow powder), with the following structural formula:

[0055]

[0056] Example 4

[0057] Similar to Example 1, except that the capping agent was 0.2 mol bromododecane, resulting in polyquaternary ammonium salt-grafted nano-Fe3O4, denoted as Fe3O4@KH550@MD5 (brownish-yellow powder), with the following structural formula:

[0058]

[0059] Example 5

[0060] Similar to Example 1, except that the capping agent was 0.2 mol bromoethane, resulting in polyquaternary ammonium salt-grafted nano-Fe3O4, denoted as Fe3O4@KH550@MD1 (brownish-yellow powder), with the following structural formula:

[0061]

[0062] Example 6

[0063] First, 1.68 g of Fe3O4 (20 nm to 50 nm) was ultrasonically dispersed in 15 mL of distilled water for 30 min, and then added to a three-necked flask containing silane coupling agent (KH550). The molar ratio of nano-Fe3O4 to silane coupling agent was 1:3. After mechanical stirring at 40 °C for 8 h, the product was removed, washed with an appropriate amount of ethanol, and then vacuum dried at 40 °C for 10 h to obtain the intermediate Fe3O4@KH550.

[0064] The second step, a one-pot method, involves sonicating the intermediate Fe3O4@KH550 in 15 mL of distilled water for 15 min. Epichlorohydrin is then added dropwise through a constant-pressure dropping funnel to a three-necked flask containing an aqueous solution of an organic amine (triethylenetetramine) and the sonicated Fe3O4@KH550. The reaction is carried out for 6 h under conditions of water bath heating at 60°C, mechanical stirring, and reflux, yielding the uncapped substance. The molar ratio of epichlorohydrin, organic amine, and intermediate Fe3O4@KH550 is 1:1.6:0.01.

[0065] The third step involved capping the uncapped material by adding bromooctane and continuing mechanical stirring in a 60°C water bath, followed by reflux for 4 hours. After the reaction was complete, the product was washed with distilled water (50 mL x 5), centrifuged at 8000 rpm, and then washed again with ethanol (50 mL x 5), centrifuged at 8000 rpm. The supernatant was discarded, and the product was removed using a magnet and freeze-dried for 24 hours to obtain polyquaternary ammonium salt-grafted nano-ferric oxide. The amount of bromooctane was three times the amount of the organic amine.

[0066] Example 7

[0067] First, 1.68 g of Fe3O4 was ultrasonically dispersed in 20 mL of distilled water for 15 min and added to a three-necked flask containing silane coupling agent (KH550). The molar ratio of nano-Fe3O4 to silane coupling agent was 1:10. After mechanical stirring at 40 °C for 8 h, the product was removed, washed with an appropriate amount of ethanol, and then vacuum dried at 60 °C for 8 h to obtain the intermediate Fe3O4@KH550.

[0068] The second step, a one-pot method, involves sonicating the intermediate Fe3O4@KH550 in 20 mL of distilled water for 30 min. Epichlorohydrin is then added dropwise through a constant-pressure dropping funnel to a three-necked flask containing an aqueous solution of an organic amine (tetraethylenepentamine) and the sonicated Fe3O4@KH550. The reaction is carried out for 6 h under conditions of water bath heating at 60°C, mechanical stirring, and reflux, yielding the uncapped substance. The molar ratio of epichlorohydrin, organic amine, and intermediate Fe3O4@KH550 is 1:2:0.02.

[0069] The third step involved capping the uncapped material by adding bromooctane and continuing mechanical stirring in a 60°C water bath, followed by reflux for 6 hours. After the reaction was complete, the product was washed with distilled water (50 mL x 5), centrifuged at 8000 rpm, and then washed again with ethanol (50 mL x 5), centrifuged at 8000 rpm. The supernatant was discarded, and the product was removed using a magnet and freeze-dried for 24 hours to obtain polyquaternary ammonium salt-grafted nano-ferric oxide. The amount of bromooctane was four times the amount of the organic amine.

[0070] Example 8

[0071] First, 1.68 g of Fe3O4 was ultrasonically dispersed in 17 mL of distilled water for 20 min, and then added to a three-necked flask containing silane coupling agent (KH570). The molar ratio of nano-Fe3O4 to silane coupling agent was 1:6. After mechanical stirring at 40 °C for 8 h, the product was removed, washed with an appropriate amount of ethanol, and then vacuum dried at 50 °C for 9 h to obtain intermediate Fe3O4@KH550.

[0072] The second step, a one-pot method, involves sonicating the intermediate Fe3O4@KH550 in 17 mL of distilled water for 20 min. Epichlorohydrin is then added dropwise through a constant-pressure dropping funnel to a three-necked flask containing an aqueous solution of an organic amine (polyethyleneimine with a molecular weight of 1800) and the sonicated Fe3O4@KH550. The reaction is carried out in a water bath at 60°C with mechanical stirring and reflux for 6 h to obtain the uncapped substance. The molar ratio of epichlorohydrin, organic amine, and intermediate Fe3O4@KH550 is 1:2:0.04.

[0073] The third step involved capping the uncapped material by adding bromooctane and continuing mechanical stirring in a 70°C water bath, followed by reflux for 5 hours. After the reaction was complete, the product was washed with distilled water (50 mL x 5), centrifuged at 8000 rpm, and then washed again with ethanol (50 mL x 5), centrifuged at 8000 rpm. The supernatant was discarded, and the product was removed using a magnet and freeze-dried for 24 hours to obtain polyquaternary ammonium salt-grafted nano-ferric oxide. The amount of bromooctane was five times the amount of the organic amine.

[0074] Example 9

[0075] First, 1.68 g of Fe3O4 was ultrasonically dispersed in 18 mL of distilled water for 25 min and added to a three-necked flask containing silane coupling agent (KH570). The molar ratio of nano-Fe3O4 to silane coupling agent was 1:8. After mechanical stirring at 40 °C for 8 h, the product was removed, washed with an appropriate amount of ethanol, and then vacuum dried at 45 °C for 9 h to obtain intermediate Fe3O4@KH550.

[0076] The second step, a one-pot method, involves sonicating the intermediate Fe3O4@KH550 in 18 mL of distilled water for 25 min. Epichlorohydrin is then added dropwise through a constant-pressure dropping funnel to a three-necked flask containing an aqueous solution of an organic amine (dimethylamine) and the sonicated Fe3O4@KH550. The reaction is carried out for 6 h under conditions of water bath heating at 60°C, mechanical stirring, and reflux, yielding the uncapped substance. The molar ratio of epichlorohydrin, organic amine, and intermediate Fe3O4@KH550 is 1:1.7:0.1.

[0077] The third step involved capping the uncapped material by adding bromooctane and continuing mechanical stirring in a 65°C water bath, followed by reflux for 4.5 hours. After the reaction was complete, the product was washed with distilled water (50 mL x 5), centrifuged at 8000 rpm, and then washed again with ethanol (50 mL x 5), centrifuged at 8000 rpm. The supernatant was discarded, and the product was removed using a magnet and freeze-dried for 24 hours to obtain polyquaternary ammonium salt-grafted nano-ferric oxide. The amount of bromooctane was 3.5 times the amount of organic amine.

[0078] In this invention, either polyethyleneimine with a molecular weight of 600 or 3000 can be used to prepare nano-ferric oxide grafted with oligomeric quaternary ammonium salt.

[0079] Testing conditions:

[0080] 1) FT-IR was performed using a Nicolet infrared spectrometer and the potassium bromide pellet method.

[0081] 2) XRD: A Bruker X-ray scanner was used, and the scanning range was 20° to 80°.

[0082] 3) XPS: The Thermo Scientific K-Alpha was used. After pressing an appropriate amount of sample into a pellet, it was attached to the sample tray. The sample was then placed in the sample chamber of the Thermo Scientific K-Alpha XPS instrument. When the pressure in the sample chamber was less than 2.0 × 10⁻⁷ mbar, the sample was sent into the analysis chamber. The spot size was 400 μm, the operating voltage was 12 kV, and the filament current was 6 mA. The full spectrum scanning pass energy was 150 eV with a step size of 1 eV; the narrow spectrum scanning pass energy was 50 eV with a step size of 0.1 eV.

[0083] 4) SEM: A German ZEISS Sigma 300 was used. A small amount of the dispersed sample was directly attached to the conductive adhesive and sputtered with gold for 45 seconds using a Quorum SC7620 sputtering coating instrument. The morphology of the sample was then photographed using a ZEISS Ge mini SEM 300 scanning electron microscope. The accelerating voltage during the photograph was 3kV and the detector was an SE 2 secondary electron detector.

[0084] The demulsification and dehydration rate effects of Examples 1-4 were tested:

[0085] Test conditions:

[0086] 1. O / W emulsion: The oil content of the treated oily wastewater was determined according to the Chinese petroleum and natural gas industry standard SY / T0530—2011 "Determination of Oil Content in Oilfield Produced Water - Spectrophotometric Method". The demulsification effects of Fe3O4@KH550@MD2, Fe3O4@KH550@MD3, Fe3O4@KH550@MD4, and Fe3O4@KH550@MD5 were evaluated, and the demulsifier with the best demulsification effect was screened. Based on this, the effects of temperature, pH, salinity, and dosage on the demulsification effect were explored.

[0087] Oil content:

[0088] Where C is the oil content, K is the absorbance coefficient, and V is the light absorption coefficient. W V0 represents the volume of the water sample being tested, E represents the absorbance, and V0 represents the total volume of the extract.

[0089] Cyclic demulsification experiment design: After the demulsification test, MNPs were collected using an external magnetic field and thoroughly washed with ethanol:distilled water (1:9) for regeneration. The MNPs were then redispersed in distilled water and sonicated for 15 minutes. The recovered MNPs were then reused in the next cycle of the demulsification test. Additionally, as a control, used MNPs were collected and directly used in the next cycle of the demulsification test to evaluate their reusability. The recovery procedure was repeated multiple times.

[0090] 2. W / O Emulsion: Referring to the Chinese petroleum and natural gas industry standards SY / T 5281—2000 "Test Method for Performance of Crude Oil Demulsifiers (Bottle Test Method)" and SY 5280-2018 "General Technical Conditions for Crude Oil Demulsifiers", the bottle test method was used to evaluate Fe3O4@KH550@MD3 synthesized by grafting different proportions of oligomeric quaternary ammonium salts onto the intermediate Fe3O4@KH550, and the optimal ratio was screened out.

[0091] Figure 2 (a) indicates a wavenumber of 2720 cm⁻¹. -1 and 2820cm -1 The stretching vibration of CH in the silane coupling agent, 1089 cm⁻¹ -1 The stretching vibration of the Si-O bond in the silane coupling agent, 629 cm⁻¹ -1 -764cm -1 The fingerprint area is due to the stretching vibration of the Fe-O bond, 3420 cm. -1 The peak represents the stretching vibration of primary amines, consistent with the basic functional groups of Fe3O4@KH550. Figure 2 The value 1464cm appears in (b), (c), and (d). -1 1469cm -1 1462cm -1 quaternary ammonium salt CN + Characteristic peaks, compared with Fe3O4 and Fe3O4@KH550, prove that KH550 was successfully grafted with MD quaternary ammonium salts of different chain lengths and iron oxide.

[0092] Figure 3The XRD diffraction patterns of Fe3O4@KH550, raw materials and oligomeric quaternary ammonium salt grafted nano-Fe3O4 were confirmed to have typical diffraction peaks at 2θ of 30.1°, 35.5°, 43.1°, 53.4°, 57.0° and 62.6°, corresponding to diffraction indices (220), (311), (400), (422), (333) and (440) (JCPDS card number: 89-0950). It can be observed that the intensity of each diffraction peak of Fe3O4@KH550@MD2, Fe3O4@KH550@MD3, Fe3O4@KH550@MD4, and Fe3O4@KH550@MD5 is reduced to a certain extent compared with Fe3O4@KH550 and Fe3O4, even leading to the near disappearance of the (422) and (622) crystal planes. This is because the encapsulation of quaternary ammonium salts with alkyl chains of different lengths reduces their crystallinity, further proving that KH550 and MD polyquaternary ammonium salts were successfully grafted onto Fe. On Fe3O4, by comparing Fe3O4@KH550 and Fe3O4@KH550, it was found that the diffraction peak intensity of Fe3O4@KH550 was greater than that of Fe3O4. This is because the crystal structure of Si atoms is a face-centered tetragonal lattice, which will produce strong and clear peak positions. Therefore, the diffraction peak intensity of the intermediate KH550 is generally greater than that of the raw material iron(III) oxide. At the same time, it was found that the (220) crystal plane of Si appeared at 47.2°. The above indicates that KH550 and MD polyquaternary ammonium salt were successfully coated on Fe3O4 nanoparticles.

[0093] Figure 4 XPS characterization spectra of Fe3O4@KH550@MD3 and Fe3O4@KH550@MD5 were obtained. Atomic % was obtained via XPS: C 1s 38.7, Fe 2p 16.67, N 1s 3.38, O 1s 38.77. Full-spectrum XPS spectra are also provided. Figure 4 In (a), it can be clearly seen that Fe3O4@KH550@MD3 and Fe3O4@KH550@MD5 XPS contain five elements: Fe, O, C, Si, and N. Figure 4 Images (b) and (c) show the C1s XPS spectra of Fe3O4@KH550@MD3 and Fe3O4@KH550@MD5, respectively, exhibiting characteristic peaks at CC 284.8 eV, C-N 288.61 eV, CO 288.61 eV, and C-Si 283.58 eV. Figure 4 Images (d) and (e) show the XPS spectra of Fe3O4@KH550@MD3 and Fe3O4@KH550@MD5 O1s, respectively, exhibiting characteristic peaks of Fe-O at 529.78 eV, CO at 530.18 eV, and Si-O at 531.75 eV. Figure 4In the middle, (f) and (g) are the XPS spectra of Fe3O4@KH550@MD3 and Fe3O4@KH550@MD5 N1s, respectively, showing characteristic peaks of N-H 402.09 eV and C-N 399.78 eV. Figure 4 In the images (h) and (i), Fe 2p of Fe3O4@KH550@MD3 and Fe3O4@KH550@MD5 are respectively shown. The images show characteristic peaks of Fe 2p1 / 2 (723.48 eV, 725.34 eV) and Fe 2p3 / 2 (712.01 eV, 710.18 eV), which are typical characteristic peaks of Fe3O4@KH550@MD3 and Fe3O4@KH550@MD5. This further proves that Fe3O4@KH550@MD3 and Fe3O4@KH550@MD5 were successfully synthesized.

[0094] Figure 5 The effect of a series of MNPs on the demulsification of O / W emulsions (high-sulfur crude oil from Changqing Oilfield). For example... Figure 5 As shown in (a)-(f), the Fe3O4@KH550@MD series products were first screened as single agents under conditions of 50-1000ppm, 60℃, and 1h. Figure 5 In (a)-(f), Fe3O4@KH550@MD3 showed the best demulsification effect, achieving 100% transmittance in the lower water layer and zero oil content at 400 ppm; at 200 ppm, the transmittance exceeded 98%. Fe3O4@KH550@MD5, a product in the same series, also demonstrated good demulsification performance. The benzyl bromide-terminated product Fe3O4@KH550@MD2 produced less clear demulsified water, achieving 90% transmittance in the lower water layer at 600 ppm. This indicates that the octane-terminated product Fe3O4@KH550@MD3 has a high chain length compatibility with Changqing high-sulfur crude oil, and longer chain termination is more conducive to migration to the oil-water interface than benzene ring termination. Simultaneously, careful dosage control and selection of the optimal range are crucial during demulsification.

[0095] Figure 6 (a)-(e) represent the demulsification effects of Fe3O4@KH550@MD3 and Fe3O4@KH550@MD5 on oily wastewater. For demulsification of oily wastewater, a dosage of MNP of 20 ppm already shows a very ideal demulsification effect, compared with... Figure 5Compared to the prepared O / W emulsions, Fe3O4@KH550@MD3 has a wider applicable pH range (pH = 2-14). The applicable pH range for Fe3O4@KH550@MD5 is (pH = 8-10). Because oily wastewater contains less oil than oil-in-water emulsions, the repulsive force between negatively charged oil droplets in the system is weaker; only a small amount of Fe3O4@KH550@MD3 is needed to neutralize the negative charge in the system. Simultaneously, due to the low oil content, pH has little effect on potential, resulting in a wider applicable range. Salinity has a synergistic effect on the demulsification of Fe3O4@KH550@MD3 (MNP). This section explores the influence of redox reactions on the demulsification of high-sulfur crude oil. Figure 6 As shown in (d), hydrogen peroxide has no synergistic effect on the demulsification of MNP. For the high-sulfur oily wastewater system, the Changqing emulsion system contains sulfur, but not free divalent sulfur. The main source of sulfur may be the polar atoms in the crude oil asphalt and resin macromolecules. C, O, and S in the asphalt readily react with O2 to generate polar functional groups such as ketones, aldehydes, carboxylic acids, pyrroles, and sulfoxides. These generate electrostatic repulsion during the asphalt oxidation process. The introduction of oxygen-containing functional groups such as CO, H2O, and SO in the oxidation products reduces the compatibility of the components, leading to asphalt aging and viscosity, and also causing the problem of oil droplets adhering to the wall during the demulsification process. The redox reaction did not enhance the effect on this system.

[0096] Finally, to explore the magnetic responsiveness of Fe3O4@KH550@MD3 and Fe3O4@KH550@MD5, a cyclic demulsification experiment was conducted on the MNP in a high-sulfur oily wastewater system. Consistent with the VSM characterization results, the MNP exhibits superparamagnetism. Figure 6 As shown in Figure (e), experiments demonstrate that after five cycles of demulsification tests, the transmittance of the lower layer water from Fe3O4@KH550@MD3 demulsification still reached 85%, and the transmittance of the lower layer water from Fe3O4@KH550@MD5 demulsification still reached 80.6%. This indicates that the recycling and reuse of MNPs is feasible. However, after multiple demulsification operations, the active sites on the MNPs become saturated due to the adsorption of asphaltenes and resin molecules onto their surface, thus causing a decrease in demulsification efficiency.

[0097] Figure 7 (a) shows the demulsification effect of the oil-cement (O / W) emulsion system. Experiments in Examples 6-9 showed that the lower layer of water after demulsification was quite turbid and yellow. This turbidity was improved after compounding with T2-MD4. An effective formulation was selected: 50 ppm [1:100-Fe3O4@KH550@MD3+T2-MD4] achieved a 97% demulsification and dehydration rate for ES emulsions at 1 hour and 60℃. Figure 7(b) shows the demulsification effect of W / O emulsion. Through experiments on Examples 6-9, Example 8 showed the best demulsification effect for W / O emulsion, with a dehydration rate of 95.8%.

[0098] Figure 8 Images (a)-(h) show the contact angle test results of the superamphilic nanoparticles used in Examples 6-9 for wettability testing. The contact angles of Examples 7, 8, and 9 with distilled water and kerosene were all less than 10°. In Example 9, the contact angle measured within 0.5 seconds was 0°. During the capture of the photograph by the contact angle measuring instrument, it was observed that oil droplets (water droplets) rapidly penetrated the MNP surface within 0.5 seconds. A superhydrophilic surface (water contact angle (WCA) of 0°-10°) represents an extreme wetting state where water can rapidly diffuse and completely wet the surface to form a thin film. Superoleophilic materials (oil contact angle (OCA) of 0°-10°) can selectively filter or absorb oil from oil-water mixtures. Metal meshes, nanomaterials, and fluoropolymers, after surface modification to increase surface roughness, can be prepared as degreasing materials. Superamphilic materials are materials where both water and oil can completely diffuse on the surface. Through surface functionalization modification, a rough surface morphology is obtained, giving the material both hydrophilic and oleophilic characteristics. Figure 8 The experimental results in (a)-(h) show that the demulsifier 1:100-Fe3O4@KH550@MD3 prepared in Example 9 has an oil-water contact angle of 0° after surface functionalization reaction, and is a superamphilic magnetic nanoparticle.

[0099] Nanostructures have a significant impact on superwetting properties. The arrangement and orientation of nanostructures can control the wetting state and movement of liquids. Superhydrophilic and superhydrophobic surfaces can be achieved by introducing multi-scale structures onto the surface of nanoparticles. MNPs, being rough surfaces containing both hydrophilic and oleophilic domains, achieve a superamphilic wetting state by covering their respective domains under the pull of the 2D capillary effect. This study explores the structure-activity relationship between MNPs and their wetting state. Starting from the design concept of MNP molecules, hydrophobic nano-Fe3O4 raw materials, after hydrolysis and encapsulation using KH550 as a medium, acquire the amphiphilic characteristics of surfactants and can migrate to the interface. To increase charge density, MD series oligomeric quaternary ammonium salts with carbon chain ends of different lengths are grafted onto them. Encouragingly, the MNPs are then endowed with a superamphilic wetting state.

[0100] This invention combines the excellent demulsification effect of oligomeric quaternary ammonium salts. The structure of polyquaternary ammonium salts offers significant advantages over small-molecule surfactant quaternary ammonium salts. By introducing polycations into the system, unlike traditional demulsifiers which require high temperature and pressure for synthesis, oligomeric quaternary ammonium salts can initiate polymerization reactions at 55-70℃. Furthermore, they possess moderate molecular weight, good stability, and are more easily coated onto the surface of magnetic nanoparticles. Surface grafting modification of nano-ferric oxide modifies the wettability of the nanoparticles, enabling demulsification in at least three different types of oil-water systems, thus expanding the applicability of the nanoparticles. Small-bottle demulsification experiments were conducted on various oil-water systems, including O / W and W / O crude oil emulsions prepared from Changqing crude oil, oily wastewater, and oil-cement systems (ES emulsions).

[0101] The superamphilic nanoparticles prepared by this invention have a wide range of applications and overcome the problem of strong specificity of traditional demulsifiers, and have the following advantages:

[0102] ① For the O / W emulsion (Changqing Oilfield high-sulfur crude oil) system, Fe3O4@KH550@MD3 has the best demulsification effect. At 400ppm, the light transmittance of the lower water layer reaches 100% and the oil content is 0; at 200ppm, the light transmittance of the lower water layer reaches more than 98%. The same series of products Fe3O4@KH550@MD5 has a good demulsification effect.

[0103] ② For O / W (oil-containing wastewater from Changqing Oilfield) Fe3O4@KH550@MD3, under conditions of 20ppm, 60℃, and 1h, the transmittance of the lower layer water can reach 99.2%. For Fe3O4@KH550@MD5, under the same conditions, the transmittance can reach 98%. After 5 cycles of demulsification tests, the transmittance of the lower layer water from Fe3O4@KH550@MD3 after demulsification can still reach 85%, and the transmittance of the lower layer water from Fe3O4@KH550@MD5 after demulsification can still reach 80.6%. This indicates that the recovery and reuse of MNP is feasible.

[0104] ③ For W / O emulsions (Changqing Oilfield crude oil), the demulsification efficiency is higher for W / O emulsions with high water content. In Example 8, the demulsification and dehydration rate of the W / O emulsion prepared with a 2:8 oil-water ratio (molar ratio) reached 95.8%.

[0105] ④ The combination of Fe3O4@KH550@MD3 and T2-MD4 improved the problem of cloudy yellow water. An effective formulation was selected: 50ppm [1:100-Fe3O4@KH550@MD3+T2-MD4] achieved a 97% demulsification and dehydration rate for ES emulsions at 60℃ for 1 hour.

[0106] The above description only illustrates the preferred embodiments of the present invention and should not be construed as limiting the scope of the claims. The present invention is not limited to the above embodiments, and variations in its specific structure are permitted. All modifications made within the scope of the independent claims of this invention are also within the scope of protection of this invention.

[0107] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

Claims

1. A method for preparing oligomeric quaternary ammonium salt-grafted nano-ferric oxide, characterized in that, Includes the following steps: Nano-iron oxide and silane coupling agent KH550 were mixed and then hydrolyzed to obtain intermediate Fe3O4@KH550. The intermediate Fe3O4@KH550, epichlorohydrin and organic amine were reacted in a one-pot process to obtain an uncapped substance. Uncapped material is added to an ethanol solution of the capping agent to carry out a capping reaction, resulting in nano-iron oxide grafted with oligomeric quaternary ammonium salt; the organic amine is dimethylamine, triethylenetetramine, tetraethylenepentamine or polyethyleneimine with a molecular weight of 600-3000.

2. The method for preparing oligomeric quaternary ammonium salt-grafted nano-ferric oxide according to claim 1, characterized in that, The molar ratio of nano-ferric oxide to silane coupling agent is 1:(3-10).

3. The method for preparing oligomeric quaternary ammonium salt-grafted nano-ferric oxide according to claim 1, characterized in that, The hydrolysis reaction takes place at a temperature of 30-60℃ for 6-8 hours.

4. The method for preparing oligomeric quaternary ammonium salt-grafted nano-ferric oxide according to claim 1, characterized in that, The molar ratio of epichlorohydrin, organic amine and intermediate Fe3O4@KH550 is 1:(1.6-2):(0.01-0.1).

5. The method for preparing oligomeric quaternary ammonium salt-grafted nano-ferric oxide according to claim 1, characterized in that, The one-pot reaction temperature is 55-70℃, and the time is 6-8 hours.

6. The method for preparing oligomeric quaternary ammonium salt-grafted nano-ferric oxide according to claim 1, characterized in that, The capping agent is bromoethane, bromohexane, bromooctane, bromododecane, or benzyl bromide; The amount of capping agent used is 3-5 times the amount of organic amine. The end-capping reaction is carried out at a temperature of 60-80℃ for 4-6 hours.

7. A nano-iron oxide grafted with oligomeric quaternary ammonium salt prepared by the method according to any one of claims 1-6.

8. The application of nano-ferric oxide grafted with oligomeric quaternary ammonium salt prepared by the method according to any one of claims 1-6 as a demulsifier in oil-water separation.

Citation Information

Patent Citations

  • Preparation method of high-interfacial-activity reverse demulsifier

    CN104370333A

  • Preparation method of natural polyphenol modified oligomeric quaternary ammonium salt demulsifier

    CN116478720A

  • Magnetic composite adsorbent for one-step separation and adsorption of emulsified oil as well as preparation method and application of magnetic composite adsorbent

    CN117123200A